Integrating Spirituality in Accounting Research: A Novel Methodological Approach - Rismawati; Pahala, Indra; Agung Ulupui, I Gusti Ketut (Fakultas Ekonomi, Universitas Negeri Jakarta, Indonesia, 2023)
Accounting research has traditionally been emphasized from a quantitative and rational perspective. However, accounting as a social science encompasses deeper and more diverse dimensions, including spirituality. This article explores the potential of integrating spiritual methodology in accounting research, considering that spirituality can provide a novel and profound perspective in understanding the realities of accounting. Utilizing hermeneutics and phenomenology approaches, this article attempts to comprehend how spirituality can be applied in accounting research and the benefits that can be derived. The findings suggest that through a spiritual approach, researchers can attain a more holistic and in-depth understanding of accounting realities. Additionally, spiritual methodology fosters self-reflection and heightened awareness in researchers, enriching the research process itself. This article contributes to the literature by offering an alternative viewpoint in accounting research methodology and emphasizing the importance of integrating spirituality in research.